Are High-Growth Firms Overrepresented in High-Tech Industries? - Sven-Olov Daunfeldt; Niklas Elert; Dan Johansson (Research Institute of Industrial Economics (IFN), 2015)
It is frequently argued that policymakers should target high-tech firms, i.e., firms with high R&D intensity, because such firms are considered more innovative and therefore potential fast-growers. This argument relies on the assumption that the association among high-tech status, innovativeness and growth is actually positive. We examine this assumption by studying the industry distribution of high-growth firms (HGFs) across all 4-digit NACE industries, using data covering all limited liability firms in Sweden during the period 1997-2008. The results of fractional logit regressions indicate that industries with high R&D intensity, ceteris paribus, can be expected to have a lower share of HGFs than can industries with lower R&D intensity. The findings cast doubt on the wisdom of targeting R&D industries or subsidizing R&D to promote firm growth. In contrast, we find that HGFs are overrepresented in knowledge-intensive service industries, i.e., service industries with a high share of human capital.
Keywords: L11; L25; 330; Entrepreneurship; Firm growth; Gazelles; High-growth firms; High-impact firms; Innovation; R&D